Convergencia y polarización. El caso Peruano: 1961 - 1996 - Odar, Juan Carlos (Estudios de Economía, 2016)
According to Growth Theory, different economies converge to the same steadystate if saving rates, depreciation and population growth are controlled. Controlling for other variables, convergence will be conditional and not absolute. If the considered economies are regions of the same country, in long-run all of them should share the same steady-state. This paper evaluates if convergence in Peru is conditioned by geographic variables. Evidence suggests that, caused by geographical factors, Peruvian regions follow different dynamics and that there are at least two economic regimes that converge to different steady-states.